Silica microchannel fabrication using fluorine based rie with alas a mask - Wan Mokhzani, Wan Norhaimi; Retnasamy, Vithyacharan; Zaliman, Sauli, Assoc. Prof. Dr.; Taniselass, Steven; Ahmad Husni, Mohd Shapri; Norazeani, Abdul Rahman; Abdul Halis, Abdul Aziz (INSInet Publications, 2013)
Link to publisher's homepage at www.aensiweb.com/‎